INTEGRATION OF ISLAMIC RELIGIOUS EDUCATION BASED ON LOCAL WISDOM: A MULTIETHNIC CASE STUDY AT STAI KUALA KAPUAS - Arbainsyah Arbainsyah; Hamdanah Hamdanah; Normuslim Normuslim; Olis Olis (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
Background: The integration of local wisdom in Islamic Religious Education (PAI) is an important issue in the context of a multiethnic society so that religious learning is not merely normative, but also contextual to the socio-cultural realities of students. Various studies have made important contributions in examining the integration of local wisdom in Islamic Religious Education learning at the elementary and secondary levels of education, while studies on the practice of such integration in the context of multiethnic universities still open up wider scope for study. Purpose of the Study: This article aims to analyze the form and process of integration of local wisdom values ​​of the Dayak, Banjarese, and Javanese ethnic groups in PAI learning at the Sekolah tinggi Agama Islam Kuala Kapuas and identify its implications for students' religious understanding. Methods: The study used a qualitative approach with a multiethnic case study design. Data were collected through in-depth interviews, observations, and documentation studies of five informants consisting of PAI lecturers, students, academic leaders, and community leaders with purposive sampling techniques, then analyzed using an interactive analysis model. Results: The results indicate that the integration of local wisdom is carried out through linking the concepts of Islamic teachings (PAI) with local cultural values, such as the philosophy of Huma Betang, the value of togetherness (baimbai), and the ethics of politeness in the learning process. Findings from interviews with five participants show that these principles serve as a meeting point for shared cultural understanding ​​that strengthen inclusive and moderate religious understanding in a multi-ethnic university environment. Conclusions: The pluralist-assimilationist approach empowers students not only to preserve their original cultural identity but also to assimilate Islamic culture in achieving an effective and sustainable multicultural education paradigm.